Adult education and community action : adult education and popular social movements - Lovett, Tom; Clarke, Chris; Kilmurray, Avila (Routledge library editions. Adult education ;, 2019)
Originally published in 1982, this book discusses the role of adult education in social and community action. In particular it presents a critical assessment of 'community education' and the theories of Illich, Freire and Gramsci and it proves that there is a radical adult education tradition in the USA, Europe and North America which can offer many insights into the contemporary debate about the role of adult learning. The material is based on a decade of practical involvement in community action and education in Great Britain and Northern Ireland, where - despite deep political and religious divisions - community action has united Catholics and Protestants in a common resolve.- Resumé vydavatel